(untitled) (Contemporary Journal of Social Science Review, 2025)
Security issues between Pakistan and Afghanistan encompass a complex array of economic, social, and other security challenges, exacerbated by historical, political, and geographical factors. Pakistan faces several national security challenges related to the management of its border with Afghanistan. These issues are primarily centred on terrorism, smuggling, illegal migration, and regional instability. Afghanistan’s instability has led to a significant refugee population in Pakistan, straining resources and causing social unrest. This research article examines the intricate dynamics of Pakistan-Afghanistan relations with a focus on land border management and its implications for Pakistan’s national security. The study employs a case study approach to explore how border management practices between the two countries impact regional stability and security. Through an in-depth analysis of historical and contemporary border issues, this paper highlights the strategic significance of the Pakistan-Afghanistan border in the context of national security concerns. The research identifies key challenges faced by Pakistan, including smuggling, cross-border terrorism, and illegal migration, and assesses how these issues undermine the country’s security and stability. It also explores the effectiveness of current border management practices and their role in mitigating security threats. The findings suggest that while existing border management strategies address some security concerns, significant gaps remain. The paper concludes with policy recommendations aimed at enhancing border security and improving relations between Pakistan and Afghanistan. These recommendations emphasize the need for collaborative efforts, increased surveillance, and strengthened diplomatic engagement to ensure a secure and stable border environment. This research contributes to the field of international relations by providing insights into the critical role of border management in shaping national security policies and regional stability.